2016
DOI: 10.3109/23320885.2016.1160785
|View full text |Cite
|
Sign up to set email alerts
|

Simple and easy reconstruction of nail matrix lesion using lateral finger flap after excision of digital mucous cyst

Abstract: We treated nine patients with skin defect produced by digital mucous cyst (DMC) excision on the finger and toe using lateral finger flap (LFF). The postoperative scars were esthetically acceptable and no recurrence of mucous cysts was observed. Our LFF is a simple method to repair minor distal dorsal finger defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…Many authors have reported operative procedures and results of DMC treatment [ 5 , 10 , 12–15 ]. Recently, osteophytectomy has been shown to be an important step in treating DMC [ 3 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have reported operative procedures and results of DMC treatment [ 5 , 10 , 12–15 ]. Recently, osteophytectomy has been shown to be an important step in treating DMC [ 3 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…LFF is reverse transposition flap which is harvested from the lateral aspect of the finger. The LFF is easy to harvest [ 12 ], but minor dog ear deformities can occur. To solve this problem, we invented an island-type LFF (iLFF).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors believe that the risk of skin necrosis is reduced by skin flaps such as a rhomboid flap, digital artery perforator flap and rotation flap, which allow excision of mucous deposits invading the thin skin overlying the cyst. Therefore, many authors advocate skin excision and the use of local flaps to cover the resulting defect [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…6 show a representative case.Outcome measuresPostoperative flap survival, incisional healing and infection were evaluated. The ROM of the DIP or thumb IP joints 2 months postoperatively was measured.Postoperative patients' satisfaction was assessed by VAS score at the least times follow-up.Statistical analysisA paired t-test was used to compare the pre-and postoperative ROMs of the DIP or thumb IP joints.Statistical significance was accepted for probabilities < 5% (P<0.05).…”
mentioning
confidence: 99%
“…Therefore, many authors advocate skin excision and the use of local flaps to cover the resulting defect [5][6][7][8][9]. Although the function of skin flaps is often more satisfactory than that of skin grafts, most of the designs and procedures for skin flaps are relatively complex.…”
Section: Introductionmentioning
confidence: 99%